Theory and Practice of Digital Libraries -- TPDL 2013 Selected Workshops LCPD 2013, SUEDL 2013, DataCur 2013, Held in Valletta, Malta, September 22-26, 2013. Revised Selected Papers - Bolikowski, Łukasz.; Bolikowski, Łukasz.; Casarosa, Vittore.; Casarosa, Vittore.; Goodale, Paula.; Goodale, Paula.; Houssos, Nikos.; Houssos, Nikos.; Manghi, Paolo.; Manghi, Paolo.; Schirrwagen, Jochen.; Schirrwagen, Jochen. (Communications in Computer and Information Science,, 2014)
This book constitutes the refereed proceedings of the selected workshops co-located with the 17th International Conference on Theory and Practice of Digital Libraries, TPDL 2013, held in Valletta, Malta, in September 2013. The volume is organized in three parts, containing the 26 revised full papers of the three workshops: Linking and Contextualizing Publications and Datasets (LCPD 2013); Supporting Users Exploration of Digital Libraries (SUEDL 2013); Moving beyond technology: iSchools and education in data curation. Is Data Curator a new role? (DataCur 2013).